La epidemia de peste a fines del siglo XVI: un análisis comparativo de los Imperios Otomano y Español - Yanar, Omur (European Scientific Journal, ESJ, 2022)
Plague is an infectious disease caused by the bacterium Yersinia pestis. It has been responsible for widespread pandemics in the world throughout history. In this regard, the plague began to affect the Ottoman Empire in phases from the middle of the 15th century and reached its peak in almost the entire empire at the end of the 16th century. Since it is not possible to deal with this whole process in one article, this article focuses on the end of the 16th century, when the plague intensified in almost the whole empire. However, this article aims to mainly analyse the process, conditions, dynamics and effects of this epidemic based on the Spanish Empire with the comparative historical method. The plague appeared in the Ottoman Empire from the 1570s and intensified between 1591-1596. In the same period, the epidemic also appeared in Spain. The outbreak hit Spain in particular between 1596-1602. The plague caused decline in agricultural production, disrupted supply chains in the Ottoman and Spanish Empires, and thus aggravated the famine conditions experienced in this period. The total number of deaths caused by the plague in the Ottoman Empire is unclear. In contrast, it is estimated nearly 500,000 people died from this epidemic, equivalent to 6-6.5% of the total population (around 8-8.5 million) in Spain. All this reveals that the plague at the end of the 16th century, at least based on Spain, did not affect only the Ottoman Empire and that this epidemic was part of an epidemic in the Mediterranean. La peste, que es una enfermedad infecciosa producida por la bacteria Yersinia pestis, ha alcanzado la dimensión de pandemia en el mundo varias veces a lo largo de la historia. En este sentido, la peste comenzó a afectar también al Imperio otomano por etapas desde mediados del siglo XV y alcanzó su punto máximo en casi todo el imperio a finales del siglo XVI. Dado que no es posible abordar todo este proceso en un artículo, el presente artículo se centra a finales del siglo XVI, cuando la peste se intensificó en casi todo el imperio. Sin embargo, este artículo pretende analizar principalmente el proceso, las condiciones, la dinámica y los efectos de esta epidemia basada en el Imperio español con el método comparativo de la historia. La peste surgió en el Imperio otomano desde la década de 1570 y se intensificó entre 1591- 1596. En el mismo período, la epidemia también surgió en España. El brote asoló a España especialmente entre 1596-1602. La peste provocó la caída de la producción agrícola, interrumpió las cadenas de suministro a los otomanos y en España y, por lo tanto, agravó las condiciones de hambre experimentadas en este período. No se puede presentar el número total de muertos causados por la peste en el Imperio otomano. Por el contrario, se ha calculado el número de muertos por la peste en unas 500.000 personas, equivalente al 6-6,5 % del total de la población (alrededor de 8-8,5 millones) en España. Todo ello revela que la epidemia de peste de finales del siglo XVI, al menos sobre la base de España, no afectó únicamente al Imperio otomano, y que esta epidemia era parte de una epidemia en el Mediterráneo.